Subcutaneous implantable cardioverter-defibrillator: is it ready for use in children and young adults? A single-centre study. Issue 12 (22nd June 2018) - Silvetti, Massimo Stefano; Pazzano, Vincenzo; Verticelli, Letizia; Battipaglia, Irma; Saputo, Fabio Anselmo; Albanese, Sonia; Lovecchio, Mariolina; Valsecchi, Sergio; Drago, Fabrizio
Abstract: Aims: Use of the subcutaneous implantable cardioverter-defibrillator (S-ICD) to prevent sudden cardiac death is increasing. Few data exist on S-ICD in young patients. We reviewed our single-centre experience in order to assess the effectiveness and safety of S-ICD implantation, and to identify potential factors associated with complications. Methods and results: Observational, non-randomized, standard-of-care study on S-ICD implantation/follow-up in young patients with inherited arrhythmias (IA), cardiomyopathies, and congenital heart defects (CHD). Fifteen patients (6 CHD, 8 cardiomyopathies, and 1 IA), median age 15 years (25th–75th centiles, 14–28), 10 of them <18 years, with body mass index (BMI) 22.6 ± 3.4, underwent S-ICD implantation (primary prevention 93%). The first six patients underwent a standard implantation procedure (three surgical incisions), the following nine a two-incision procedure. No intraoperative complications occurred. Over 12 (7–24) months follow-up, two patients received appropriate shocks and one (7%) inappropriate shock. Four patients had device-related complications requiring surgical intervention: three skin erosions at the superior parasternal incision, one pocket infection. A higher risk of complications was seen in patients who underwent standard procedures [hazard ratio (HR) 4.98, 95% confidence interval (CI) 1.53–47.36; P  = 0.0482] and those with BMI <20 (HR 9.44, 95% CI 0.95–93.23; P  = 0.0169). Conclusion: S-ICD implantation was safe and effective in young patients with low rates of inappropriate shock. However, the risk of device-related complications during follow-up remains substantial in patients with low BMI. To prevent possible complications, a two-incision technique should be preferred.